2000
DOI: 10.1016/s0740-5472(99)00026-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral couples therapy for alcoholism and drug abuse

Abstract: Behavioral couples therapy (BCT) sees the substance-abusing patient with the spouse to arrange a daily "sobriety contract" in which the patient states his or her intent not to drink or use drugs and the spouse expresses support for the patient's efforts to stay abstinent. BCT also teaches communication and increases positive activities. Research supports three conclusions. First, BCT for both alcoholism and drug abuse produces more abstinence and fewer substance-related problems, happier relationships, fewer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
217
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(227 citation statements)
references
References 19 publications
4
217
0
6
Order By: Relevance
“…Furthermore, inviting the significant other into treatment also helps the clinician assess and mitigate any domestic violence that may be occurring (Fals-Stewart and Kennedy 2005;O'Farrell and Fals-Stewart 2000;Senreich and Vairo 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inviting the significant other into treatment also helps the clinician assess and mitigate any domestic violence that may be occurring (Fals-Stewart and Kennedy 2005;O'Farrell and Fals-Stewart 2000;Senreich and Vairo 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 15 years, the vast majority of the studies that have examined the effectiveness of couple's therapy among clients in substance abuse treatment have focused on behavioral couples therapy (BCT), a standardized behavior-oriented couples therapy approach that focuses both on the dynamics of the couple's relationship and the use of substances by the identified client, and that typically involves 15-20 couples sessions over a period of 5-6 months , 2009aO'Farrell and Fals-Stewart 2000). Recently, Fals-Stewart et al (2009b) compared samples of gay men and lesbian women in outpatient alcohol treatment randomly assigned to either BCT (along with an individual therapy component) or to only an individual behavioral treatment modality (IBT) in regard to alcohol use outcomes, relationship adjustment, and client satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In Press(In Press):e58786. 5 lationships (25). To better identify the nature of the added support necessary for these individuals, future research should explore the effects of specific familial environmental factors, such as socialization, socioeconomic status, and treatment stigma, on illicit opioid use in MMT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, for children with behavior problems, two different studies of parenting interventions (of the Incredible Years and Triple P) have found that when couples were in distressed relationships, adding curriculum content that focused on the couple's relationship led to an increase in the intervention's effects on parenting (Webster-Stratton and Taylor 2001). Similarly, a head-to-head test of two substance abuse treatment models found that treatment was more effective when the spouse of the substance abuser was trained to be supportive in the treatment process (O'Farrell and Fals-Stewart 2000).…”
Section: Strengthening Relationships Of Low-income Couples: Two Pathsmentioning
confidence: 99%